Massive Hemoptysis in a Case of Intralobar Pulmonary Sequestration Associated with Pulmonary Hypoplasia and Meandering Right Pulmonary Vein: Diagnosis and Management - Manoranjan Mohapatra; Sanjeet Mishra; Paresh Jena (Case Reports in Pulmonology)
Pulmonary sequestration is a congenital malformation characterized by focal area of dysplastic lung tissue that lacks normal communication with tracheobronchial tree and receives blood supply from systemic arteries. Surgical resection has been the conventional method of treatment of pulmonary sequestration. In recent years transarterial embolization of the anomalous systemic arteries has emerged as a suitable alternative to surgery. In this paper, we describe transarterial coil embolization for control of massive life-threatening hemoptysis in a rare case of intralobar sequestration in right lung associated with ipsilateral pulmonary hypoplasia and meandering right inferior pulmonary vein. A 3-year follow-up computed tomographic (CT) angiography revealed complete regression of the sequestration along with altered pulmonary arterial contour. To the best of our knowledge, transarterial coil embolization for control of massive life-threatening hemoptysis in such a complex pulmonary anomaly has not yet been reported.